KEBERHASILAN SAMBUNG PUCUK ALPUKAT (Persea americana mill) DENGAN BERBAGAI TEKNIK SUNGKUP - Salawati, Salawati; H.D Ahmad, Sutarmin; Tony, Tony; Dayanti, Sry (Fakultas Pertanian Universitas Ratu Samban, 2023)
Shoot splicing is the most effective way for propagation of avocado plants at this time. Its success can reach 80-90%. This study aims to determine the influence of the type of hood on the success of connecting avocado shoots. This research was carried out in BP DAS assisted seed breeding. Central Sulawesi Provincial Watershed in Tolitoli Regency, for 4 months in 2022 using a group random environment design (RGD) of 5 treatments labeled Po without a lid, P1, pocong hood, P2 tie hood, P3 ordinary hood, P4 cow bed hood, each treatment is repeated 3 times, each trial unit consists of 7 plants, the data collected are analyzed using a variety analysis or F test, if there is a difference, proceed with the smallest real difference test (SRD). The results showed that the treatment of ordinary hoods, pocong, and cow beds affected the success of connecting avocado shoots for the parameters of increasing seedling height, number of leaves, stem diameter and survival percentage. Keywords: Avocado seeds, grafting, hood.